2009
DOI: 10.1590/s0034-72802009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento aditivo do ceratocone por 'crosslinking' do colágeno após implante de anel de Ferrara

Abstract: RESUMOObjetivo: Este trabalho tem como objetivo relatar experiência com utilização do crosslinking após implante de anel intracorneano de Ferrara (Ferrara Ophtalmic) visando a melhora refrativa e estabilização corneana. Métodos: Seis pacientes com idade entre 26 e 38 anos foram submetidos ao tratamento com crosslinking após implante de anel de Ferrara. Cinco pacientes receberam 2 segmentos de anel e um paciente recebeu um segmento. Depois de 4 a 55 meses os pacientes foram submetidos a aplicação do "crosslinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Differences in the indications for transplantation can be related to the study period and the location of the service, as there are regional variations in public health conditions and the accessibility of services. A recently-developed procedure to prevent corneal degeneration by keratoconus is corneal crosslinking, which can halt its progress even after implantation of an intracorneal ring, helping to reduce the demand for transplantation (15) . Improved contact lenses can also help reduce the number of keratoplasties due to keratoconus.…”
Section: Dendrogram Of Variablesmentioning
confidence: 99%
“…Differences in the indications for transplantation can be related to the study period and the location of the service, as there are regional variations in public health conditions and the accessibility of services. A recently-developed procedure to prevent corneal degeneration by keratoconus is corneal crosslinking, which can halt its progress even after implantation of an intracorneal ring, helping to reduce the demand for transplantation (15) . Improved contact lenses can also help reduce the number of keratoplasties due to keratoconus.…”
Section: Dendrogram Of Variablesmentioning
confidence: 99%
“…Several studies have demonstrated its safety, stability, and ability to improve corneal topography and tomography indices, as well as corrected visual acuity (CVA) (7)(8)(9)(10)(11) . CXL has also been suggested as an adjunctive therapy to rigid contact lenses and intrastromal corneal ring segment implantation (12) . However, complications related to the procedure, although infrequent, have been observed; they include scars and corneal opacities, persistent epithelial defect and, more rarely, bacterial keratitis (13,14) .…”
mentioning
confidence: 99%